2021
DOI: 10.1021/acsnano.1c04005
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Fabricated microPlates for Prolonged, Intra-articular Matrix Metalloproteinase 13 siRNA Nanocarrier Delivery to Reduce Post-traumatic Osteoarthritis

Abstract: Post-traumatic osteoarthritis (PTOA) associated with joint injury triggers a degenerative cycle of matrix destruction and inflammatory signaling, leading to pain and loss of function. Here, prolonged RNA interference (RNAi) of matrix metalloproteinase 13 (MMP13) is tested as a PTOA disease modifying therapy. MMP13 is upregulated in PTOA and degrades the key cartilage structural protein type II collagen. Short interfering RNA (siRNA) loaded nanoparticles (siNPs) were encapsulated in shape-defined poly(lactic-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 80 publications
(143 reference statements)
2
26
0
Order By: Relevance
“…DEX-μPLs effectively protected articular cartilage and joint structure in the PTOA model. Not only that, μPLs could also carry short interfering RNA (siRNA) loaded nanoparticles (siNPs) of MMP13 ( Figure 4 ) (Bedingfield et al., 2021 ). The findings showed that it could remain in the PTOA model for more than 10 days and maintained down-regulation of the MMP13 gene and reduced levels of MMP13 protein in the joints throughout the 28-day study.…”
Section: Drug Delivery System (Dds) For Oa Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…DEX-μPLs effectively protected articular cartilage and joint structure in the PTOA model. Not only that, μPLs could also carry short interfering RNA (siRNA) loaded nanoparticles (siNPs) of MMP13 ( Figure 4 ) (Bedingfield et al., 2021 ). The findings showed that it could remain in the PTOA model for more than 10 days and maintained down-regulation of the MMP13 gene and reduced levels of MMP13 protein in the joints throughout the 28-day study.…”
Section: Drug Delivery System (Dds) For Oa Therapymentioning
confidence: 99%
“…Duvall et al. attached a Col2 monoclonal antibody (mAbCII) to the surface of polymeric siRNA nanoparticle complexes (siNPs) (Bedingfield et al., 2021 ). They build a nanoparticle that could target and penetrate cartilage with approximately 100 nm and approximately zeta potential.…”
Section: Drug Delivery System (Dds) For Oa Therapymentioning
confidence: 99%
“…It was hypothesized that the unique flat shape and mechanical property of the particles complementarily aided in the process of lubrication (Figure 5 ; Di Francesco et al, 2021 ). Additionally, the same particles were used for delivering matrix metalloproteinase 13 (MMP‐13) interfering RNA loaded nanoparticles (siMMP13‐NPs) in the same animal model (Bedingfield, Colazo, Di Francesco, et al, 2021 ). In particular, the authors demonstrated that the combination of siRNA NPs with microparticles (siMMP13‐NPs loaded μPLs) significantly increased the residence time in the joint compared with the free NPs.…”
Section: Oa Treatment Via Nano/micromedicinesmentioning
confidence: 99%
“…In particular, the authors demonstrated that the combination of siRNA NPs with microparticles (siMMP13‐NPs loaded μPLs) significantly increased the residence time in the joint compared with the free NPs. Also, the gene silencing effect of siMMP13‐NPs loaded μPLs in‐vivo was maintained for 28 days after a single IA injection, thereby reducing all the problems associated with MMP‐13 activities in the progression of the disease itself (Bedingfield, Colazo, Di Francesco, et al, 2021 ). Different polymers including chitosan or synthetic materials like PEG, poly(caprolactone) (PCL), and poly(propylene sulfide) (PPS) have been utilized to develop similar slow releasing platforms.…”
Section: Oa Treatment Via Nano/micromedicinesmentioning
confidence: 99%
“…The researchers also designed small interfering RNA (siRNA)-loaded nanoparticles (siNPs) that were encapsulated in shape-defined poly(lactic-co-glycolic acid) (PLGA)-based microplates to maintain siNPs in the joint significantly longer than delivery of free siNPs. They enabled long-lasting therapy for post-traumatic OA by silencing MMP13 ( Bedingfield et al, 2021a ). Li et al constructed a responsive MS@G5-AHP/miR-140 “nano-micron” combined microfluidic gene-hydrogel microspheres (MSs) to alleviate the degradation of articular cartilage as a novel strategy for regional gene therapy ( Li et al, 2022 ).…”
Section: Novel Nanotherapeutic Strategies For Oa Therapymentioning
confidence: 99%